Simulation Training in Obstetrics and Gynecology: What's Happening on the Frontline?. Issue 3 (September 2017) - Wilson, E.; Janssens, S.; Hewett, D.G.; Jolly, B.; Beckmann, M.
Abstract : ( Aust N Z J Obstet Gynaecol. 2016;56(5):496–502) The purpose of this study was to investigate the current availability and utilization of simulation training as well as attitudes and perceived barriers and enablers to simulation in Australia and New Zealand, considering there is evidence that experience with surgery is suboptimal in trainees. The study was conducted using a survey that was distributed to obstetrics and gynecology trainees and fellows and collected demographic data, current exposure to simulation, and beliefs about simulation training.